A corpus-based study of morphological productivity of English language chemical engineering textbooks / Norrihan Sulan - Sulan, Norrihan (2011)
The effective teaching of word identification requires the acquisition and mastery of specific word identification skills. The aim of this study is to determine the patterns of complex words which, because of the large number of meanings signaled by word derivations, are the foundation for decomposition skills. It also aims to develop lexical knowledge of words with complex composition through the study of morphologically productive affixes in chemical engineering textbooks. It seeks to find the most productive morphological categories in the specialized corpus created and to find the density of complex words and their morphological patterns.